Pemberdayaan Ekonomi Masyarakat melalui Pendampingan Produksi Sabun Cuci Baju di Desa Kutambelin Kecamatan Naman Teran Kabupaten Karo - Safnah Soleha; Fathiya Syahidah Nasution; Al Ramzy; Hilda Zahra Lubis; Siti Aisyah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Economic empowerment of rural communities is an important approach in encouraging increased welfare and household independence. Kutambelin Village in Naman Teran District, Karo Regency, has sufficient human resource potential, especially among housewives, but this has not been balanced with sustainable productive economic activities. This Community Service Program (KKN) was carried out with the aim of equipping the community with practical skills through assistance in producing laundry soap as an alternative home business. The method used in this activity is a community-based research approach with a qualitative descriptive design that includes initial observation, program socialization, practice-based training in soap making, and simple assistance related to packaging and the economic value of the product, which was attended by 27 PKK mothers and the Kutambelin Village community. The results of the activity showed an increase in community understanding and skills in the process of making laundry soap, accompanied by a change in mindset towards business opportunities based on daily needs, where the implementation of soap making became an attraction in itself to make and market it, because it is easy and the ingredients are easy to obtain. The resulting soap products can be used for household needs and have the potential to be developed as a micro-scale business. Thus, this activity demonstrates that mentoring simple skills can be an effective strategy in supporting community economic empowerment.